2015
DOI: 10.1124/mol.115.098970
|View full text |Cite
|
Sign up to set email alerts
|

Gedunin Binds to Myeloid Differentiation Protein 2 and Impairs Lipopolysaccharide-Induced Toll-Like Receptor 4 Signaling in Macrophages

Abstract: Recognition of bacterial lipopolysaccharide (LPS) by innate immune system is mediated by the cluster of differentiation 14/ Toll-like receptor 4/myeloid differentiation protein 2 (MD-2) complex. In this study, we investigated the modulatory effect of gedunin, a limonoid from species of the Meliaceae family described as a heat shock protein Hsp90 inhibitor, on LPS-induced response in immortalized murine macrophages. The pretreatment of wild-type (WT) macrophages with gedunin (0.01-100 mM, noncytotoxic concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 105 publications
(115 reference statements)
1
6
0
Order By: Relevance
“…Recently, it was reported that 1 suppressed the activation of macrophages through binding to myeloid differentiation protein 2 (MD-2), and not by affecting TLR4-mediated signaling. Their data supports our results of inhibitory effects of 1 on NO production in LPS-activated macrophages [ 60 ]. In addition, the structural requirements of limonoids ( 1 – 17 ) with regard to inhibition of LPS-induced NO production in mouse peritoneal macrophages and TNF-α-induced cytotoxicity in L929 cells were found to show different tendencies as mentioned above.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, it was reported that 1 suppressed the activation of macrophages through binding to myeloid differentiation protein 2 (MD-2), and not by affecting TLR4-mediated signaling. Their data supports our results of inhibitory effects of 1 on NO production in LPS-activated macrophages [ 60 ]. In addition, the structural requirements of limonoids ( 1 – 17 ) with regard to inhibition of LPS-induced NO production in mouse peritoneal macrophages and TNF-α-induced cytotoxicity in L929 cells were found to show different tendencies as mentioned above.…”
Section: Discussionsupporting
confidence: 92%
“…LPS binding thus promotes the dimerization of TLR4 and MD-2. TLR4 not only mediates responses to LPS, a major cellular component of Gram-negative bacteria, it is also involved in inflammatory responses to various other substances, such as ligands of harmful factors produced by Gram-positive bacteria and fusion protein (F protein) of respiratory syncytial virus [18,26,51]. In addition, individuals with a TLR4 D299G polymorphism are at increased risk of septic shock induced by Gram-negative bacteria infections.…”
Section: Tlr4mentioning
confidence: 99%
“…However, eritoran failed its phase III clinical trial because there was no obvious improvement with the compound over placebo . Some natural and synthetic chemicals, such as curcumin , JSH , gedunin and xanthohumol , and two new compounds, L6H21 and L48H37 , which we investigated in our laboratory, bind directly to the MD‐2 hydrophobic pocket and showed obvious anti‐inflammatory activity in that they displace LPS from MD‐2. In this study, we found that L2H21 is an inhibitor of MD‐2 (Figs and ).…”
Section: Discussionmentioning
confidence: 99%